Assessing the Performance of School-to-Work Transition Regimes in the EU - Kari P Hadjivassiliou; Arianna Tassinari; Werner Eichhorst; Florian Wozny (Institute for the Study of Labor (IZA), 2016)
The Great Recession that has engulfed Europe since 2008 has had a profound impact on the process of young people's school-to-work (STW) transition. Countries' institutional configurations considerably matter in shaping the structure of young people's STW transitions and mediating the impact of the Great Recession on youth unemployment. Drawing upon Pohl and Walther's concept of 'youth transition regime' (2007), we have assessed the performance of selected EU countries belonging to different clusters regarding the speed, ease and quality of STW transitions. Differences in performance across regimes exists, with some faring better than others, although at the same time a common, worrying trend can be identified across clusters, comprising a progressive deterioration of the quality of youth transitions across the board, despite the positive policy intentions to strengthen and improve the efficacy of transition regimes.
Keywords: I2; J23; J24; 330; school-to-work; youth unemployment; transition regime; European Union